(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Introduction: Following its initial pilot implementation in 2017, the “Living well with COPD” self-management programme has been scaled nationwide by the Swiss Lung Associations since 2019. The aim of this mixed-methods study was to evaluate the real-world effectiveness and the experience of new coaches with the programme until February 2025. Method: The programme incorporates six weekly group modules provided by a coach, followed by four phone-calls. It aims to support patients in managing their disease and adopting healthy lifestyle behaviours, including increasing physical activity. To evaluate the effectiveness, we assessed disease specific quality of life (Chronic Respiratory Questionnaire, CRQ), exercise capacity (1-min sit-to-stand test, 1-min STS), symptoms (COPD Assessment Test, CAT), number of exacerbations (<1 year), and change in smoking behaviour from baseline to programme end (after 14 months). We conducted personal interviews to assess the coaches’ experience with specific programme elements. Results: Twelve Cantonal Lung Associations included in total 446 persons with COPD (mean age 68 years, 56% female), 290 patients completed follow-up assessments. The patients showed statistically significant improvements in the CRQ subscales fatigue (p = 0.005), mastery (p = 0.001), 1-min STS (p < 0.001), and CAT (p = 0.03), but no change in the other scales was observed. Fifteen persons stopped smoking (p = 0.01). Eleven coaches (82% female) were interviewed (mean duration interviews: 56 minutes). They assessed that the modules in general covered the most relevant topics, but suggested to consider additionally nutrition, incontinence, depression, and palliative care. They highly appreciated the Action Plan to improve physical activity, but for some coaches the implementation remained challenging, especially due to the different activity levels of the patients. In about half of the patients, the motivation to be more physically active improved over time. The coaches attributed the reasons to a better understanding of the relevance of physical activity and the ability to set realistic activity goals. Conclusions: The “Living well with COPD” programme was successfully implemented nationwide in real-world settings and showed a positive impact on health status. While the significance of incorporating physical activity into patient education was unequivocal to the coaches, more comprehensive training on how to address this topic is warranted. Support/Funding Source: This study was funded by the foundation Health Promotion Switzerland. Keywords: Self-management programme, physical activity action plan, COPD, implementation evaluation, patient education